Cost‐effectiveness of professional oral health care in Australian residential aged care facilities. (21st December 2018) - Münzenmayer, Melisa A.; Mariño, Rodrigo; Hsueh, Arthur
Abstract : Objective: To conduct a model‐based cost‐effectiveness analysis, from a health care system perspective, of using oral health professionals to provide oral hygiene services at residential aged care facilities (RACFs) in Victoria, Australia, compared to current practice (CP). Background: Increasingly dentate cohorts of older adults are entering RACFs, making urgent the need of further development and provision of oral health programmes in ageing dentitions. Materials and Methods: The model was based on 47 624 RACFs' places in Victoria over one year. The main outcome measured was "cost per pneumonia case averted." Four different scenarios of oral hygiene provision were compared to CP. Costs included were RACF staff training, professional salaries, programme coordinator office expenses, dental equipment and hospitalisation costs. Effectiveness assumptions for each scenario were based on systematic reviews and randomised control trials. Results: All four scenarios were dominant strategies. The magnitude of negative incremental cost‐effectiveness ratio was not informative; therefore, incremental costs and incremental effectiveness were used to present results. "Professional oral health care (POHC) provision once every two weeks and current provision of oral health care the other days" was the most cost‐saving alternative (AU $896 per resident saved). The most effective alternative was "POHC provision once a week and non‐POHC provision by trained Nurse aids twice per day the other days" (6779 pneumonia cases averted). One‐way sensitivity analyses confirmed the robustness of results. Conclusion: The four scenarios were highly cost‐effective compared to CP. These results could be a strong basis to implement new oral health programmes in Australian RACFs.